Martianera, Óscar. “Del sentido de la genealogía” - Mateo Prada Quintero (Ideas y Valores)
Martianera, Óscar. "Del sentido de la genealogía", Diánoia [Universidad Nacional Autónoma de México] 49/53 (2004): 57-69.